2017
DOI: 10.1007/s00300-017-2170-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent occupation by Adélie Penguins (Pygoscelis adeliae) at Hope Bay and Seymour Island and the ‘northern enigma’ in the Antarctic Peninsula

Abstract: We excavated active and abandoned Ade ´lie Penguin (Pygoscelis adeliae) colonies at Seymour Island and Hope Bay, Antarctic Peninsula, to determine an occupation history for this species at these sites. Previous research at Hope Bay has indicated an occupation there since the middle Holocene, based on a sediment record from Lake Boeckella. Excavations revealed only shallow and relatively fresh ornithogenic soils in the active colonies at the two localities. At least 53 abandoned pebble mounds were located at Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…yr BP (Emslie et al, 2011; Figure 1). Although there was only minimal movement of juvenile penguin bones from breeding sites on the terrace near the Pingfo I beach deposits, ornithogenic soils from these former colonies are absent, adding to the mismatch with depositional records for penguin breeding (including those in lake sediments, beach deposits, and glacial moraines) that has been termed the 'northern enigma' (Emslie et al, 2018). Only one active breeding colony of Adélie penguins at the Danger Islands, Weddell Sea (Figure 1), has produced an older age of ornithogenic soils at ~2800 cal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…yr BP (Emslie et al, 2011; Figure 1). Although there was only minimal movement of juvenile penguin bones from breeding sites on the terrace near the Pingfo I beach deposits, ornithogenic soils from these former colonies are absent, adding to the mismatch with depositional records for penguin breeding (including those in lake sediments, beach deposits, and glacial moraines) that has been termed the 'northern enigma' (Emslie et al, 2018). Only one active breeding colony of Adélie penguins at the Danger Islands, Weddell Sea (Figure 1), has produced an older age of ornithogenic soils at ~2800 cal.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al (2017) reported the recovery of juvenile Gentoo penguin bones from Ardley Lake, Ardley Island, dating to ~7400–7200 cal. yr BP, though no ornithogenic soils have been found near this lake or on Ardley Island that also date to this period (Emslie et al, 2018). Tatur (1989) also reported ~2 m of alluvial deposits of sands and gravels that included at the base a ~40 cm thick phosphatic mud containing abundant juvenile Adélie and Chinstrap penguin bones from Penguin Ridge, Thomas Point, King George Island.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations